2022
DOI: 10.5713/ab.22.0262
|View full text |Cite
|
Sign up to set email alerts
|

Direct-fed Enterococcus faecium plus bacteriophages as substitutes for pharmacological zinc oxide in weanling pigs: effects on diarrheal score and growth

Abstract: Objective: Effects of direct-fed Enterococcus faecium plus bacteriophages (EF-BP) were investigated as potential substitutes for pharmacological ZnO for weanling pigs. Methods: Dietary treatments were supplementations to a basal diet with none (NC), 3,000ppm ZnO (PC), 1×10 10 colony-forming units of E. faecium plus 1×10 8 plaque-forming units (PFU) of anti-Salmonella typhimurium bacteriophages (ST) or 1×10 6 PFU of each of anti-enterotoxigenic Escherichia coli K88 (F4)-, K99 (F5)-, and F18-type bacteriophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…In pig production, stressful changes in weaned pigs leads to immune system dysfunctions and decreased piglet health and growth performance (Campbell et al, 2013). The findings of this study are consistent with previous reports (Yan et al, 2012;Oh et al, 2022). Supplementing bacteriophages in the diet of nursery pigs to replace colistin did not affect the ADFI, the ADG, or the FCR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In pig production, stressful changes in weaned pigs leads to immune system dysfunctions and decreased piglet health and growth performance (Campbell et al, 2013). The findings of this study are consistent with previous reports (Yan et al, 2012;Oh et al, 2022). Supplementing bacteriophages in the diet of nursery pigs to replace colistin did not affect the ADFI, the ADG, or the FCR.…”
Section: Discussionsupporting
confidence: 90%
“…Bacteriophages are proposed as a way to control pathogenic bacteria in the swine farming industry (Kim et al, 2017;Oh et al, 2022). Several studies have shown that bacteriophage therapy can significantly reduce the E. coli and Salmonella spp.…”
Section: Advances Inmentioning
confidence: 99%